Determination Ethanol In Arak With Gas Chromatography - Nyoman Sudarma; I Made Oka Adi Parwata (Bali Medika Jurnal, 2017)
Ethanol is a type of alcohol that can be consumed. One of drinks containing ethanol is Arak. Due to ethanol drink containing in excessive levels, has many causes and event such as accidents caused by drunken brawl. The purpose of this research was to determine the levels of ethanol in Arak is sold in the Merita village of Karangasem regency. Determination levels of ethanol done by gas chromatography. Results of the determination of levels ethanol of 5 samples taken at random to meet the standard required by Menkes RI number  86/Menkes/Per/IV/77, alcohol group B at the rate of 5-20% is sampel ‘a’ that is at the rate of 18.47%, sample ‘c’ with the  rate of 16.11% and sampel ‘d’ with the rate 11.68%. Alcohol group C with 20-55% rate that is in the sample ‘b’ with a sample rate of 25.28% and sampel ‘e’ with the rate 25.94%.